Meta-Analisis : Pengaruh Pembinaan Career Development Terhadap Kinerja Guru: Penelitian - Taufik, Nur; Setiawan, Antonius Hendy; Bektiarso, Singgih; Budiarso, Aris Singgih; Siswati, Bea Hana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to comprehensively analyze the effect of career development coaching on teacher performance through a meta-analysis approach. The research was conducted using a systematic literature review of 10 relevant scientific articles, which were examined to identify key findings related to teacher performance. The selected studies consisted of indexed international journals, accredited national journals, and national publications that met methodological standards. The results of the meta-analysis indicate that career development coaching has a positive and significant effect on teacher performance. Career development programs are proven to enhance professional competence, work motivation, job satisfaction, and the effectiveness of instructional implementation. Several studies also reveal that motivation and job satisfaction function as additional variables that strengthen the relationship between career development and teacher performance. Career development coaching is a strategic factor that consistently contributes to improving teacher performance. Structured, sustainable, and teacher-oriented career development programs are capable of enhancing professionalism and the overall quality of learning.